Molecular cloning and sequencing of mRNAs coding for minor adult globin polypeptides of Xenopus laevis. - Knöchel, W (1983)
Globin mRNA was isolated from immature red blood cells of an adult Xenopus laevis female. mRNA/cDNA hybrids were integrated in the Pst I cleavage site of pBR 322 by G/C tailing, and cloned in Escherichia coli strain HB 101. By restriction site analysis as well as hybridization behaviour we identified two clones coding for minor adult alpha and beta globin chains. Nucleotide sequence analysis and derived amino acid sequences are presented.